SURFACE ROUGHNESS AND GLOSS OF CURRENT CAD/CAM RESIN COMPOSITES BEFORE AND AFTER TOOTHBRUSH ABRASION - Ahmed Saleh Alfehaid; Mona Aqlaa Alenazi; Abeer Moahammed Alonizi; Nashmeah shweash Alenazi; Eman jamaan Alanazy; Rajaa Mohammed Alsalem; Gahan safer alotaibi; Munira Naif Thaar ALnefaie (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Objective: evaluate and compare the surface roughness of two different nano-hybrid composites composite before and after tooth brushing simulation.Materials and Methods: Twenty dimensionally standardized composite specimens of two nano-hybrid resin composites (TetricEvoCeram and Admira Fusion) were used. Ten specimens from each composite group. All specimens were polished and then subjected to a tooth brushing simulator wear test. Surface roughness (Ra) were measured before tooth brushing and after 5000, 10, 000, 15, 000, and 20, 000 tooth brushing cycles. The data was analysed using two-way ANOVA to assess surface roughness values and pair wise comparisons in the form of Tukey post hoctests were performed to interpret main effects. Results: For all tested materials, surface roughness increased after tooth brushing wear test. Surface roughness (Ra) values ranged from 0.17 to 0.22 µm at baseline and increased to between 0.44 and 0.49 µm after 20, 000 tooth brushing cycles. The lowest initial Ra value was detected in TetricEvoCeram.Conclusions: Simulated tooth brushing wear led to an increase in surface roughness for all tested composite materials. TetricEvoCeram had smoother surface after polishing and following 20, 000 cycles of tooth brushing wear whereas, Admira Fusion demonstrated rougher surface before and after tooth brushing abrasion.